Newborn Screening for Congenital Hypothyroidism, Congenital Adrenal Hyperplasia, and Glucose-6-Phosphate Dehydrogenase Deficiency for Improving Health Care in India - Verma, Jyotsna; Roy, Papai; Thomas, Divya C.; Jhingan, Geetu; Singh, Azad; Bijarnia-Mahay, Sunita; Verma, Ishwar C. (Journal of Pediatric Intensive Care, 2020)
Newborn screening (NBS) aims toward early detection of treatable congenital disorders. From January 2008 through December 2017, 13,376 newborns were screened for congenital hypothyroidism (CH), congenital adrenal hyperplasia (CAH), and glucose-6-phosphate dehydrogenase (G6PD) deficiency at Sir Ganga Ram Hospital, India, by measuring G6PD activity, thyroid-stimulating hormone, and 17-hydroxyprogesterone on dried blood specimens. The birth prevalence of 1:2,000 for CH, 1:2,500 for CAH, and 1:125 for G6PD deficiency indicates the latter as the most prevalent. Performance evaluation of testing reveals a robust screening program with 100% sensitivity and >99% specificity. Hence, we recommend NBS for early diagnosis and treatment to prevent adverse outcomes.
Keywords: congenital adrenal hyperplasia; G6PD; hypothyroidism; newborn screening